A study on the development of avionics for the past 30 years - 394197 Fadhilah Ismail (Skudai : Universiti Teknologi Malaysia, 2000)
Project Paper (Bachelor of Mechanical Engineering (Aeronautical)) - Universiti Teknologi Malaysia, 2000